Vicarious and Source Credibility: A Cross Cultural Explanation - (:unkn) unknown (My University, 2014)
Two factors represent orientations of credibility elements, vicarious and source credibility. Both orientations include credibility elements: competence, trustworthiness, and goodwill/care. The two factor solution (vicarious = x axis; source = y axis) develops a credibility grid based on five classifications of credibility evaluations. The five credibility grid evaluations are defined by cross-cultural communication theory. Quantitative evidence is derived from three tests (a) the model, (b) the function, and (c) classification. Data from questionnaries involving 1,149 participants are analyzed both within and across US, Spanish, and Japanese cultures. Reliabitliy estimates for US (.75) and Spanish (.63) are stable, but deficient for Japanese (.50) data. A paired-sample t-test both within and across cutlures identify vicarious and source credibility as significantly different, and factor analysis indicates the model is stable. Means and correlation analysis indicate that each of the cultures vary in function related to theory. Classification results from discriminant analysis, where vicarious and source become a single function, identify new grounds for cross-cutlural communication research. Overall results provide new grounds for credibility research by including vicarious credibility as an advancement to source credibility.
Keywords: Credibility; Cross-Cultural; Intercultural; Social Influence; Source; Vicarious